Seismic behavior of reinforced concrete columns with light transverse reinforcement under different lateral loading directions - Pham, Thanh Phuong (2014)
Considerable progress has been made on the strength and ductility research of reinforced concrete (RC) columns over the last two decades. However, the seismic performance of RC columns under lateral loading in different directions remains limited. This paper presents an experimental and numerical investigation carried out on RC columns with light transverse reinforcement with an emphasis on how varying the directions of seismic loading influences the seismic failure mechanisms of the columns. Seven half-scale RC columns were tested with the columns subjected to axial load and cyclic forces under reversed double-curvature bending. The parameters varied in the test program included the axial load ratio and loading directions. The overall performance of each specimen is examined in terms of cracking patterns, hysteretic response, initial stiffness, shear strength, drift ratio at axial failure, and energy dissipation capacity. A three-dimensional (3-D) finite element (FE) model is developed to supplement the experimental results. The direction of seismic loads is found to have a significant effect on the drift capacities and failure modes of both rectangular and square columns. The extent of change in the shear resistance capacity resulting from the different angles of seismic load could be predicted. A simple upper limit for shear strength contributed by concrete is proposed.